Development of functional yogurt fortified with wheat germ and strawberry as functional ingredients - Hashemi Gahruie, Hadi; Hadi Eskandari, Mohammad; Mesbahi, Gholamreza (Progress in Nutrition, 2019)
The aim of present study was to evaluate the effect of adding wheat germ to functional yogurt, which is well-known as a miraculous food around the world. For this purpose, seven functional formulations containing wheat germ (0, 10, 20 and 30% based on dry matter) were produced by adding wheat germ to yogurt samples after and before fermentation. The results showed that adding wheat germ to functional yogurt led to an increase in the amount of such fortified compounds as ferric, potassium, zinc, phosphorous, magnesium, unsaturated fatty acids and fiber. Moreover, the addition of wheat germ did not have a significant effect on the acidity profile and growth of starter culture. The results of sensory evaluation indicated that addition of wheat germ after fermentation significantly increased the acceptability of yogurt samples. It is thus concluded that the prepared functional yogurts can be highly effective in supplying the nutritional needs of the age groups under nine years-old.